2006
DOI: 10.1007/s10562-006-0071-5
|View full text |Cite
|
Sign up to set email alerts
|

The Role of CaO in the Ziegler–Natta Catalyst for Propylene Polymerization

Abstract: A certain amount of CaO enhanced the activity of Ziegler-Natta catalyst during propylene polymerization, but decreased isotacticity. The results indicated that CaO accelerated the initial polymerization rates and improved catalyst against deactivation without effects on melting point, crystallinity and morphology of polypropylene. The electron spin resonance (ESR) results revealed that CaO facilitated the reduction of Ti 4+ species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Thus, the expected sequence of catalytic activity was TEA > TiBA > TnOA. The noticeable difference of catalytic activity among these three cocatalyst types was observed as seen in many previous works using only TiCl 4 as a titanium precursor. The obtained sequence can be explained by polymerization method.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…Thus, the expected sequence of catalytic activity was TEA > TiBA > TnOA. The noticeable difference of catalytic activity among these three cocatalyst types was observed as seen in many previous works using only TiCl 4 as a titanium precursor. The obtained sequence can be explained by polymerization method.…”
Section: Resultssupporting
confidence: 66%
“…Many research fields have involved with this kind of catalyst including improvement of catalytic activities, characterization techniques, and development of a novel support . In addition, numerous related factors such as polymerization temperature, cocatalyst types, and Al/Ti ratios are also crucial to optimize for the enhancement of catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to elucidate the effect of fumed silica, the in situ ESR measurement was performed. ESR is one of the most powerful techniques used to measure the oxidation of Ti 3+ , especially upon the in situ condition [13]. In this measurement, the catalyst samples having different amounts of fumed silica added were activated by TEA based on polymerization condition.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the ZN catalyst preparation process has attracted great academic and industrial interest because of its influence on the catalytic activity, kinetics of olefin polymerization, and final polyolefin properties [11,12]. The picture emerging from the above studies supports that activity and morphology of ZN catalysts are depended on many factors such as the type of alcohol in the adduct, dealcoholation method, crystal structure of support, process of synthesis and the presence of different components [2,8,[13][14][15]. In this regard, studies revealed that in catalyst preparation process, some parameters such as injection temperature of TiCl 4 and internal donor and their amount, temperature program, and the type and amount of the solvent are effective factors which affect on the performance of the resulted ZN catalyst [16,17].…”
mentioning
confidence: 99%